Co-working spaces and cultural differences - Ferreira, A. I.; Duarte, H.; Pereira, N. (BAM 2021conference proceedings, 2021)
This study aims to contribute to the existing literature by providing a deeper understanding of the links between the multiple layers in organizational culture and the different Co-working characteristics. The research presented here develops a new taxonomy of Co-working spaces by integrating results from qualitative semi-structured interviews supported by previous theoretical and empirical research. We conducted interviews with 44 owners or founders of co-working spaces. A thematic analysis revealed three different approaches to co-working, namely a profit-oriented perspective, a community-oriented perspective and a hybrid pattern that combines both perspectives. Drawing upon the interaction models, our findings contribute to a better understanding of how Co-working cultures are developed and modified in order to attract and retain Co-working members in an increasingly competitive market. Accordingly, future research should validate the proposed model with complimentary methodologies (e.g., questionnaires) and longitudinal designs to track how Co-working culture persists or changes over time.